An Experimental and Numerical Study on Glass Frit Wafer-to-Wafer Bonding - Seyed Amir Fouad Farshchi Yazdi; Matteo Garavaglia; Aldo Ghisi; Alberto Corigliano (Micromachines, 2023)
A thermo-mechanical wafer-to-wafer bonding process is studied through experiments on the glass frit material and thermo-mechanical numerical simulations to evaluate the effect of the residual stresses on the wafer warpage. To experimentally characterize the material, confocal laser profilometry and scanning electron microscopy for surface observation, energy dispersive X-ray spectroscopy for microstructural investigation, and nanoindentation and die shear tests for the evaluation of mechanical properties are used. An average effective Young’s modulus of 86.5 ± 9.5 GPa, a Poisson’s ratio of 0.19 ± 0.02, and a hardness of 5.26 ± 0.8 GPa were measured through nanoindentation for the glass frit material. The lowest nominal shear strength ranged 1.13 ÷ 1.58 MPa in the strain rate interval to 0.33 ÷ 4.99 × 10<semantics>−3</semantics> s<semantics>−1</semantics>. To validate the thermo-mechanical model, numerical results are compared with experimental measurements of the out-of-plane displacements at the wafer surface (i.e., warpage), showing acceptable agreement.